Charity Adams Earley papers - Earley, Charity Adams, 1918-2002.; Earley, Charity Adams, 1918-2002.
Correspondence, speeches, notes, military records, press clippings, printed matter, and other papers relating to Earley's experience as the first African-American commissioned officer in the Women's Army Corps during World War II and to her community activities later in life. Includes drafts of Earley's memoir One Woman's Army : a Black Officer Remembers the WAC, in which she recounts her experiences as a woman and as an African American in the segregated military at Fort Des Moines, Iowa, and as commanding officer of the 6888th Central Post Battalion stationed in Birmingham, England, and in Rouen and Paris, France.
African American army officer, educator, and civic activist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: United States. -- Army -- African American troops; United States. -- Army -- Women; United States. -- Army. -- Women's Army Corps; United States. -- Army. -- Women's Army Corps. -- Central Postal Battalion, 6888th.; African Americans -- Segregation; World War, 1939-1945 -- England -- Birmingham; World War, 1939-1945 -- France -- Paris; World War, 1939-1945 -- France -- Rouen; World War, 1939-1945 -- Participation, African American; World War, 1939-1945 -- Participation, Female; Fort Des Moines (Iowa); United States -- Armed Forces -- African American officers; Army officers; Civic activists; Educators